Three new species of the genus Passeroptes Fain (Astigmata: Dermationidae) from China - Wang, Zi-Ying; Mu, Ning; Su, Xiao-Hui; Liu, Huai (Zootaxa, 2014)
Three new species of the genus Passeroptes (Acariformes: Dermationidae) are described from passerine birds (Passeriformes) in China: Passeroptes formosus sp. nov. from Garrulax formosus formosus (Verreaux) (Guizhou), P. poecilorhynchus sp. nov. from Garrulax poecilorhynchus berthemyi (David and Oustalet) (Guizhou), and P. picae sp. nov. from Pica pica sericea Gould (Henan). Passeroptes garrulax is redescribed from Garrulax poecilorhynchus berthemyi in Guizhou.